A Systematic Review of Depth-Dependent Cytoprotection with Therapeutic Hypothermia for Cerebral Ischemia. - Parranto, Marin R.; Kung, Tiffany F.C.; Liddle, Lane J.; Khalid, Tayyaba; Thorkelsson, Aline B.; Klahr, Ana C.; Almekhlafi, Mohammed; Colbourne, Frederick (Therapeutic Hypothermia & Temperature Management, 2026)
Preclinical studies show that therapeutic hypothermia (TH) effectively reduces cerebral ischemic injury. In contrast, TH has not been consistently beneficial in clinical trials of stroke and cardiac arrest, perhaps from suboptimal dosing (e.g., delay, depth, and duration), among other factors. This systematic review aimed to find an optimal depth of TH from in vivo adult preclinical studies of global and focal ischemia. To study depth, without other confounds, we examined studies that compared ≥2 depths of TH versus normothermic controls. Our primary outcomes were infarct size (focal ischemia) and hippocampal cell death (global ischemia), while secondary outcomes were behavior, edema, and striatal cell death. Studies were assessed with the SYRCLE Risk of Bias tool (e.g., use of blinding) and additional indices of translational rigor (e.g., use of aged animals). Thirty studies were included from a search of the PubMed database in 2025. Many studies were rated as exhibiting a high risk of bias with low translational rigor. Overall, TH provided considerable protection on all endpoints, sometimes up to 100%, but no consistent dose–response patterns emerged, nor was an optimal depth of cooling readily evident. To explore the latter finding, specifically sampling variability, we conducted Monte Carlo simulations using the pooled standard deviation of the preclinical studies to generate three populations based upon a theoretical 5% protection per 1°C relationship (37°C vs. 32°C vs. 27°C groups run 75 times). Dose-dependent effects were statistically detectable in only 36% of comparisons, which showed comparably noisy patterns of protection. Thus, the variable dose-dependent effects in the reviewed animal studies likely arise, at least partially, from sampling error owing to using small samples from variable populations (average n = 8/group in focal ischemia). Overall, these findings highlight weaknesses in the extant dose–response literature that limit our ability to precisely guide clinical trials.